Strategy to Increase Employee Productivity through Sustainable Training in Kediri Ikat Woven Fabric MSMEs - Sri Hardiningrum, Iing; Churiyah, Madziatul (Universitas Islam Kadiri, 2024)
In an era of increasingly fierce competition and rapid technological change, productivity is the key to the success of companies and individuals. Human resources are considered the main asset of an organization because their abilities and skills influence the company's success. The Bandar Kidul Kediri Ikat Woven Fabric Industry has great potential but often faces challenges in increasing productivity to remain competitive. Through continuous training, MSMEs can improve employee skills, develop efficient production processes, and respond well to market changes. It is hoped that the results of this research will provide new insights into efforts to increase employee productivity in Ikat Woven Fabric MSMEs and offer practical recommendations to stakeholders to implement sustainable training programs to increase the competitiveness and growth of MSME businesses.